Impactos da urbanização na qualidade da água: uma análise dos rios Tietê e Tamanduateí na Região Metropolitana de São Paulo - Melo, Larissa Contente de (Universidade Federal de São Carlos, 2025)
The incipient planning results in environmental degradation due to impermeabilization and changes in the dynamics of hydrographic basins. This problem, combined with the inadequate treatment of liquid effluents, alters the quality of water bodies. The accelerated urbanization of the Metropolitan Region of São Paulo (MRSP) directly impacts the water quality of aquatic environments. Considering the need to promote water management, this study analyzed the changes in the Tietê and Tamanduateí rivers between 1985 and 2023, using data from the Environmental Company of the State of São Paulo (CETESB) and the Brazilian Institute of Geography and Statistics (IBGE), as well as land use and land cover maps from MapBiomas data. The results indicate an increase in urbanization, accompanied by a reduction in vegetation and an intensification of anthropic activities. The discharge of effluents and soil impermeabilization have worsened water pollution, reflected in the deterioration of the Water Quality Index (WQI) and the increase in nitrogen and phosphorus concentrations, favoring eutrophication. Seasonal variation in water quality was also observed, with improvement during flood periods. There is an urgent need for sustainable urban planning and efficient environmental practices to mitigate the impacts of urbanization and promote the recovery of water resources. Measures such as preserving green areas, effluent treatment, and reducing impermeabilization are essential to ensure water sustainability and improve the quality of life in impacted areas. Therefore, it is evident that although urbanization is inevitable, its planned and sustainable management is fundamental for environmental preservation and water quality, essential for the well-being of present and future generations.
Impacts of urbanization on water quality: an analysis of the Tietê and Tamanduateí rivers in the Metropolitan Region of São Paulo
Keywords: Qualidade da água; Urbanização; Rios Tietê e Tamanduateí; Poluição hídrica; Gestão ambiental; Water quality; Urbanization; Tietê and Tamanduateí rivers; Water pollution; Environmental management; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA